Beyond the Edge of the Century: The Postcolonial Imagination in the “New” Fictions of the Canadas - Carmona Rodríguez, Pedro M. (Miscelánea: A Journal of English and American Studies, 2008)
Whereas the 1990s witnessed the establishment of the basic parameters within which Canada could be considered a postcolonial enclave, the new millennium, shortly after its opening, has seen the reworking of the Canadian postcolonial. The contemporary rethinking of the postcolonial condition of Canada has given place to new theoretical moves, partly uncovered when looking at the long-standing mutual nurture between theoretical and imaginative writing. This paper centres on this contemporary theoretical revision to eventually propose that this revisionary invigoration has mainly been launched from fictions by authors indirectly affected by the multicultural agenda of the 1980s and 1990s. As a corollary of the reconfiguration of the Canadian postcolonial, and its views on nation, culture and identity in the negative, the fictions published in the late 1990s and the early years of the new millennium show a penchant for writing the nation in multifarious forms that gradate the (post)colonial, while bringing to the fore regional and communal histories silenced for the welfare of the national/state mirage.